Case Report: Metastasis to pleura and mediastinal lymph nodes from breast secretory carcinoma: 10 years follow-up - Huang, Fengbo; Zhao, Jing; Lian, Jie; Hong, Bo; Yu, Xiaoyan; Ma, Xiaojing; Lai, Jiabin; Qian, Wei; Tu, Jinglian; Qiu, Fuming; Zou, Hong; Huang, Jian; et al. (Frontiers in Oncology, 2025)
Breast secretory carcinoma (BSC) is a rare low-grade malignancy that frequently exhibits the ETV6::NTRK3 fusion gene and rarely presents with distant metastasis. In this report, we describe a case of 72-year-old female diagnosed with BSC, who presented with pleura and mediastinal lymph node metastases 10 years after undergoing radical mastectomy and radiotherapy. The primary tumor was characterized by a microcystic and solid architecture, eosinophilic secretions, and vacuolated cytoplasm. Immunohistochemistry (IHC) confirmed positivity for S-100 and pan-TRK. A decade later, respiratory symptoms prompted a PET/CT scan that detected metabolically active metastases in pleura and mediastinal lymph nodes. Pleura mass biopsy revealed the same morphology and IHC profile (S-100+/pan-TRK+), confirming metastatic BSC. GATA3 and TRPS1 overlap with salivary gland tumors necessitates PET/CT for distinguishing the origin. Pan-TRK IHC and NTKR3 gene break positive confirmed secretory carcinoma. Following distant metastasis, immunotherapy combined with chemotherapy was initiated. After two treatment cycles, the patient was evaluated as having stable disease after two treatment cycles, but disease progression occurred in the later four cycles. The treatment was changed to entrectinib targeted therapy, the PET/CT re-examination showed partial remission. This case highlights the rare metastatic risk of BSC and the diagnostic necessity of integrating clinical, imaging, histopathology, and NTRK3 break-apart probe detection. Targeted therapies including NTRK3 inhibitors, show promise emphasizing the importance of multidisciplinary management for this malignancy. Awareness of BSC’s metastatic potential and tailored therapeutic strategies are crucial for optimizing outcomes.